2017
DOI: 10.1177/1045389x17721029
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of mortar beams with randomly distributed superelastic shape memory alloy fibers

Abstract: The addition of fibers to cementitious composites can provide improved ductility, energy dissipation, and resistance to cracking. However, it is also important to minimize residual deformations and provide crack-closing capabilities when the material is subjected to cyclic loading. In this study, the behavior of mortar mixtures with randomly distributed superelastic shape memory alloy fibers was investigated. Superelastic shape memory alloys are metallic alloys that possess unique characteristics such as the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Some of these applications require small-diameter SMA wires. For example, several researchers have investigated the use of short SMA fibers with a diameter ranging from 0.2 to 1 mm in cementitious composites to provide crack-recovery as well as recentering capabilities (Sherif et al, 2017, 2018). However, most applications of SMAs for civil structures require large-size elements.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these applications require small-diameter SMA wires. For example, several researchers have investigated the use of short SMA fibers with a diameter ranging from 0.2 to 1 mm in cementitious composites to provide crack-recovery as well as recentering capabilities (Sherif et al, 2017, 2018). However, most applications of SMAs for civil structures require large-size elements.…”
Section: Introductionmentioning
confidence: 99%
“…Sherif et al [ 27 ] performed an experimental investigation on the performance of mortar mixtures reinforced with different volume fractions of SMA fibers under cyclic loading. They found that the mortar reinforced with SMA fibers exhibited considerable improvements in ductility.…”
Section: Application Of Niti Smas In Civil Infrastructuresmentioning
confidence: 99%
“…The development of superelastic SMA fibers is still in its early stage, where strands and wires (Daghash and Ozbulut, 2016;Sherif et al, , 2018 were mostly considered. Bonding is critical issue that cannot be easily resolved because form-setting of superelastic SMA fibers is difficult and expensive and often requires special treatment such as annealing.…”
Section: Sma Fibersmentioning
confidence: 99%